Wyznaczanie optymalnego czasu trwania inwestycji rzeczowych - Siedlecki, Rafał; Słoński, Tomasz (The Investment's Optimal Duration Problem, 2007)
This paper deals with investment's optimal duration problem. In order to find optimal solution three popular investment valuation methods (NPV, IRR, NPV∞) were used. While estimating cash flow forecast, the authors took advantage of logistic function. Investment's optimal duration depends on reinvestment rate assumption.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 139-147